Kebijakan Pengelolaan Jaringan Digital Untuk Meningkatkan Niat Berbagi Pengetahuan Antar Pegawai - Angela Caroline; Agus Gunawan; Yoke Pribadi Kornarius (Jurnal Manajemen Maranatha, 2022)
The paradigm shift from the resource-based economy to the knowledge-based economy requires companies to manage their knowledge. Knowledge management practices consist of discovering, recording, sharing, and applying them, where knowledge sharing activities are considered as the most important component in the practice of knowledge management. The intention to share knowledge within the company can be supported by adequate information technology infrastructure, where the use of information technology infrastructure has increased since the work-from-home policy was implemented during the COVID-19 pandemic. This research aims to show the influence of information technology infrastructure on the intention to share knowledge in the MSME group compared to large enterprises and recommend information technology infrastructure management policies in order to increase the intention to share knowledge among employees. This research uses survey method to observe social phenomena related to employee responses to the information technology infrastructure components provided by the company and their intention to share knowledge. Respondents for this study consisted of 617 employees in the service sector from various companies in the MSME and Large Enterprise groups. The data are analyzed using descriptive statistical tests and inferential statistical tests, namely regression tests and differential tests. The results show that there is a relationship and influence between the information technology infrastructure variables on the intention to share knowledge. Based on the Mann-Whitney U test, the perception of employees of the MSME group on the information technology infrastructure variable tends to be higher than that of the Large Enterprise group. This is due to the large number of MSMEs in Indonesia that utilize cloud computing technology. On the other hand, MSMEs need to prepare a clear division of roles in managing information technology infrastructure.